Asante market women directed and produced by Claudia Milne. - Boaitey, Charlotte.; Milne, Claudia.; Milne, Claudia.; Margolyes, Miriam. (Ethnographic video online, 1982)
As retailers, wholesalers, and negotiators, Asante women of Ghana dominate the huge Kumasi Central Market amid the laughter, argument, colour and music. The crew of this 'Disappearing World' film have jumped into the fray, explored, and tried to explain the complexities of the market and its traders. The success of this crew is impressive. As the film was to be about women traders, an all female film crew was selected and the rapport between the two groups of women is remarkable. The relationship was no doubt all the stronger because the anthropologist acting as advisor to the crew, Charlotte Boaitey, is herself an Asante. The people open up for the interviewers telling them about their lives as traders, about differences between men and women, their perception of their society and also about marriage. The women control the market through Queen Mothers who are leaders of particular sections of the market such as the yam or tomato sections.